A field-deployable mobile molecular diagnostic system for malaria at the point of need. Issue 22 (10th October 2016) - Choi, Gihoon; Song, Daniel; Shrestha, Sony; Miao, Jun; Cui, Liwang; Guan, Weihua
Abstract : A field-deployable, standalone, sample-in-answer-out molecular diagnostic system (AnyMDx) to enable quantitative molecular analysis of blood-borne malaria at the point of need. Abstract : In response to the urgent need of a field-deployable and highly sensitive malaria diagnosis, we developed a standalone, "sample-in-answer-out" molecular diagnostic system (AnyMDx) to enable quantitative molecular analysis of blood-borne malaria in low resource areas. The system consists of a durable battery-powered analyzer and a disposable microfluidic compact disc loaded with reagents ready for use. A low power thermal module and a novel fluorescence-sensing module are integrated into the analyzer for real-time monitoring of loop-mediated isothermal nucleic acid amplification (LAMP) of target parasite DNA. With 10 μL of raw blood sample, the AnyMDx system automates the nucleic acid sample preparation and subsequent LAMP and real-time detection. Under laboratory conditions with whole-blood samples spiked with cultured Plasmodium falciparum, we achieved a detection limit of ∼0.6 parasite per μL, much lower than those for the conventional microscopy and rapid diagnostic tests (∼50–100 parasites per μL). The turnaround time from sample to answer is less than 40 minutes. The AnyMDx is user-friendly requiring minimal technological training. The analyzer and the disposable reagent compact discs are cost-effective, making AnyMDx a potential tool for malaria molecular diagnosis under field settings for malaria elimination.